Hubungan Jenis Persalinan dan Prematuritasdengan Hiperbilirubinemia di RS Persahabatan - Roselina, Elsa; Pinem, Saroha; Rochimah, Rochimah (UI Scholars Hub, 2013)
Hyperbilirubinemia refers to an excessive level of accumulated bilirubin in the blood and is characterized by jaundice, or icterus, a yellowish discoloration of the skin and other organs. There are two risk factors that related to hyperbilirubinemia. Those factors are maternal factor and neonates‟ factor. The aim of this research knew which variables which catagorized as maternal factor and neonates‟ factor that related to hyperbilirubinemia in Persahabatan hospital. This research used medical records from 216 neonates and his/her mother from October 2008 until October 2009 as samples. Research design was case control, with used 5% level of significant and 80% power. The statistical analysis was multivariable logistic regression. Factors that related to hyperbilirubinemia in Persahabatan hospital were type of labor (p value 0.000) and prematurity (p value 0.022). Type of labor is a dominant variable that related to hyperbilirubinemia and neonates from un-spontaneous labor has probability to be hyperbilirubinemia 50.193 times than neonates from spontaneous labor after controlled by prematurity (odds ratio 50.193).